(untitled) (Global Journal of Human-Social Science, 2023)
Intelligence is critical in the state s decision-making process and national security strategy Nevertheless the contemporary regional and geopolitical complexity implies countless challenges to intelligence Carl von Clausewitz said In the fast-moving complex environment the target has changed by the time you adopt a plan Clausewitz 1832 Today this sentence has more relevance We live in an interregnum period where the domination of liberal democracy is challenged from the inside out through the war in Ukraine a decline of trust in democracy inequality division of societies decay of economic development rising inflation and geopolitical competition between great powers Today we live in a hazy space where there is no clear line between war and peace Further we started our twenty-first century with a dangerous relationship between political leaders and their intelligence advisors in which they are distorting intelligence information to justify their political decisions Both Prime Minister Tony Blair and President George W Bush came under unprecedented public scrutiny in both Britain and the United States and were widely charged with purposefully distorting intelligence information to justify their decision to make war on Iraq in April 2003 Scott and Jackson 2004 The need for a better understanding of both the nature of the intelligence process and its importance to national and international security policy has never been more apparent